Libraries Achieve Equilibrium Between Digital And Print As Budgets Advance - McKendrick, Joseph (Unisphere Research, 2016)
This new study of 284 community public library managers and librarians was conducted by the Library Resource Guide (LRG)—in conjunction with Unisphere Research, the market research division of Information Today, Inc. (ITI). The survey, which was administered in during the September-November 2015 time period among libraries listed in ITI’s American Library Directory, reveals current spending patterns for public, academic, government, and special libraries, and provides projections for budgets and spending trends for 2016. This report is a subset of a larger study, which included a total of 827 libraries, including academic, special, and government agency libraries, along with public libraries.
McKendrick, Joseph. "Libraries Achieve Equilibrium Between Digital And Print As Budgets Advance: The Library Resource Guide Benchmark Study On 2016 Community Public Library Spending" (New Jersey: Unisphere Research, 2016). Electronic Records, Valdosta State University. PDF (eBook).
Keywords: Libraries